Linguistic Landscape in Bandung Geology Museum - Kuraesin, Uning (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Landscape linguistics (LL) is one of the disciplines that studies the use of language in public spaces. This study will discuss the use of language in information that describes objects as historical relics in the Bandung Geological Museum from the perspective of LL and provide answers to questions about what language is used in information in the Bandung Geological Museum, what the use of these languages ​​is like in terms of size, and how the configuration of the placement of these languages ​​is positionally. The Geological Museum is a museum that presents various information about aspects of the earth and is the only museum in Indonesia. The Geological Museum is one of the educational tourism destinations in Bandung City, West Java. The Geological Museum is located at Jalan Diponegoro Number 57, Cihaur Geulis, Cibeunying Kaler District, Bandung City. This study uses a qualitative descriptive method. A study based on an approach to the focus and phenomena analyzed by emphasizing the description of the language used, and the function of the linguistic landscape in the description of each object in the Geological Museum. The results of this study show that the linguistic landscape used in this museum is four language variations, namely Indonesian, English, Latin, and Dutch. These languages ​​are written monolingually with 1 (one) sign, bilingual Indonesian-English variation 17 (seventeen) signs, and multilingual 2 (two) language signs. The size of the language signs used for the names of stones using Indonesian is larger. This aims to make the name easy to read and striking, so that it can be distinguished from other languages ​​and information.